Antenas monopolo planar com patch em anel circular para sistemas UWB - Silva, Bruna Alice Lima da (2010)
The microstrip antennas are largely used in wireless communication systems due to their low cost, weight, less complex construction and manufacturing, in addition to its versatility. UWB systems have emerged as an alternative to wireless communications over short distances because they offer of higher capacity and lower multipath distortion than other systems with the same purpose. Combining the advantages of microstrip antennas to the characteristics of UWB, it is possible to develop more and more smaller devices, with diverse geometries to operate satisfactorily in these systems. This paper aims to propose alternatives to microstrip antennas for UWB systems operate in the range between 3.1 and 10.6 GHz, with a patch on circular ring. Some techniques are analyzed and employed to increase the bandwidth of proposed antenna: the insertion of a parasitic elements and a rectangular slit in the displaced ground plane. For this, key issues are presented as the basic principles of UWB systems, the fundamental theory of antennas and microstrip antennas. The simulations and experimental characterization of constructed antennas are presented, as well as analysis of parameters such as bandwidth and radiation pattern